PERFORMANCE EFFICIENCY OF QUALITY CONTROL LABORATORY THROUGH IMPLEMENTATION OF LEAN OPERATION - Dita Ayu Lestari; Athor Subroto (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2022)
Lean operation is the common method to increase operational's efficiency, but it is still rarely implemented for Quality Control Laboratory. This paper used Value Stream Mapping to identify added value and non-added value activities from raw material analysis in Quality Control Laboratory of pharmaceutical industry. Efficiency was measured by reducing the turnaround time for raw material analysis and then converted into labor cost efficiency. Our research renders a decrease of 42.7% in turnaround time for the top 20 raw materials sample that received in 2020. In addition, it reduced the cost of labor by IDR 130,193,977 per year. These results showed us the importance of implementing lean operations in the laboratory to support pharmaceutical industries in producing quality and affordable drug products.